Recurrent scrotal edema in liver cirrhosis - Qi, Xingshun; An, Shu; Li, Hongyu; Guo, Xiaozhong (AME Medical Journal; Vol 2 (August 2017): Ame Medical Journal, 2017)
Liver cirrhosis is a potentially lethal disease, which can be complicated by liver failure, hepatic encephalopathy, splenomegaly, variceal bleeding, ascites, and hydrothorax (1,2). Herein, we reported a rare case with liver cirrhosis presenting with recurrent scrotal edema probably due to an extremely albumin level.